Uma História de Amizade & Amor - Jéssica Ferreira Alves; Róbson Pereira da Silva (Albuquerque (online), 2024)
Resenha do livro: BEAUVOIR, Simone de. As inseparáveis. 1. ed. Rio de Janeiro: Record, 2021.